Myeloid dendritic cells in severe aplastic anemia patients exhibit stronger phagocytosis. Issue 12 (18th October 2021) - Sun, Yingying; Wu, Chengcheng; Liu, Chunyan; Wang, Huaquan; Zhang, Yang; Zhang, Yu; Ran, Ningyuan; Shao, Zonghong
Abstract: Background: A deeper understanding of the pathogenesis of severe aplastic anemia (SAA) is urgently warranted to achieve better therapeutic effects. The objective of this study was to investigate the phagocytosis of myeloid dendritic cell (mDC) in SAA patients. Methods: Myeloid dendritic cells were induced in vitro from bone marrow mononuclear cells from 26 SAA patients and 12 normal controls (HCs). The phagocytosis of mDCs was detected by flow cytometry using FITC‐Dextran (40KD), and its correlation with the immune status and severity of the disease was analyzed. Results: The phagocytosis of mDC from untreated SAA patients was significantly stronger than that from complete remission group and HC group ( p  < 0.05). There was no statistical difference between the latter two groups ( p  > 0.05). The phagocytosis of mDC from SAA patients correlated positively with the concentration of interleukin (IL)‐2 ( r  = 0.389, p  < 0.05), and IL‐4 ( r  = 0.556, p  < 0.05), negatively with CD4 + /CD8 + ratio ( r  = −0.421, p  < 0.05). It also had negative correlations with the level of hemoglobin ( r  = −0.393, p  < 0.05), white blood cell ( r  = −0.436, p  < 0.05), platelet ( r  = −0.431, p  < 0.05), and reticulocyte ( r  = −0.447, p  < 0.05). The phagocytosis of mDC does not correlate with the response to IST. Conclusions: The increased phagocytosis of mDC in untreated SAA patients may contribute to abnormal activation of T helper (Th) and subsequent cytotoxic T lymphocyte (CTL) activation in these patients. It may be involved in the immune pathogenesis of SAA. Abstract : Under the stimulation of antigenic or other factors, the phagocytosis of myeloid dendritic cells in newly diagnosed SAA patients was enhanced, which facilitates the polarization of Th0 to Th1, the activation of CTL, and finally the apoptosis of hematopoietic cells.